Systems for superficial protection of concretes - Moreira, Pedro M. (2006)
Nowadays, it is consensual that the biggest degradation of concrete happens from outside to inside actions, due to the penetration of moisture, active gases and aggressive ions, by mechanical, physical and chemical causes that frequently act together. A low porosity, permeability and concrete penetration to moisture and gases are the first lines of defence against several deterioration mechanisms. The durability of concrete depends largely on how hard or easy fluids (water, carbon dioxide, oxygen) in liquid or gas form can migrate through the concrete hardened mass. When selecting the paint coating for concrete protection, importance is given to the properties of diffusion and permeability resistance, besides the properties of durability and chemical resistance. The paint coatings must stop the penetration of water and delay the influence of aggressive agents (CO2, SO2, Cl- ions), allowing the structure to breathe by a water vapour diffusion mechanism. Through tests of capillarity absorption, immersion absorption, porosity, water and oxygen permeability, a comparison was made between painted and non painted concrete specimens. Three different coating types were tested: silicon varnish; acrylic and epoxy paints. The results showed that, in general, all coatings reduce the porosity and the permeability. The epoxy paints proved to be the best ones.